Pengembangan SDM Melalui Minat dan Motivasi Santriwati pada Yayasan Taufidzul Qur’an Ar-Rahmani di Ciputat Tangerang Selatan - Lies Sunarmintyastuti; Hugo Aries Suprapto (Peneliti.net, 2020)
The Purpose of this research is to explain about implementation concept from development of manpower through their interest and motivation at Taufidzul Qur’an Ar Rahmani Institution. The method for this research is Qualitative descriptive. The data has been collected by interview, quisioner, direct observation and also documentation. The method for credibility data on the reseach is using Triangulation method which is comparison between the result of direct interview and comparison betweenthe result of interview, summary of the result for quisioner data with documents that has been prepared before. Data analytical that has been using for this research is interactive analysis which is reduction data, presentation of data and summary of conclusions. Through this research, its known that the development of human resources at Taufidzul Qur’an Ar-Rahmani Institution are using various program in practice on the field or theory. Top program at Taufidzul Qur’an Ar-Rahmani Institution is Tafidzul Qur’an 30 Juz for boarding student. Term for this program is 6 years and after finished the program will graduating from the Institution. Then program how to learning Al-Qur’an also will giving to the community near the Institution. And then boarding studentalso get enterpreneurship knowledge in theory and practice with business partner and hopefully they can change their thought about enterpreneurship and also living indipendently in the future. We are hoping that Taufidzul Qur’an Ar-ramani Institution can contribute for moslem community especially for orphan anddhuafaand also theycan produce good students who remembered and understand the content of Al-Qur’an and able to apply it in their daily life. Beside of the education of Al-Qur’an, We also hoping Taufidzul Qu’ran Ar-ramani Institution can develop formal education and knowledge of enterpreneurship (Theoritical and practical) for their students. So in the future their students able to living indipendently, creating employment for theirself and others, has good manner and also has high education.